MENINGKATKAN STANDAR PROSES MELALUI PELAKSANAAN SUPERVISI AKADEMIK PADA JENJANG SEKOLAH DASAR - Muhabbabe M (Jurnal Pendidikan Sang Surya, 2022)
The purpose of this study was to find out about improving process standards through the implementation of academic supervision at the elementary school level in Gantarang District, Bulukumba Regency. Data collection methods, namely observation, tests, and documentation. This research was conducted from January to April 2018. The research method is descriptive statistical analysis techniques and percentages. The results showed that the teacher's ability to make lesson plans in the first cycle was 78.60 percent and increased in the second cycle by 84.47 percent. The ability of teachers to apply lesson plans in the first cycle was 76.83 percent and increased in the second cycle by 82.72